Stability of ipilimumab in its original vial after opening allows its use for at least 4 weeks and facilitates pooling of residues. (May 2016) - Bardo-Brouard, Pascale; Vieillard, Victoire; Shekarian, Tala; Marabelle, Aurélien; Astier, Alain; Paul, Muriel
Abstract: Purpose: Well-documented stability data of monoclonal antibodies are generally missing. That is why we studied the physicochemical and biological stability of undiluted ipilimumab (IPI) in glass vial (5 mg/ml) over 28 d after opening, stored at 4°C and 25°C. Method: A stressed study (60°C) was performed to validate our analytical methods as 'stability indicating'. The different methods used were turbidimetry, dynamic light scattering (DLS), second-derivative ultraviolet and chromatographic methods as size-exclusion chromatography (SEC) and cation-exchange (CEX). Biological characterisation was performed by an in vitro functional binding inhibition bioassay. Results: We demonstrated that ipilimumab in opened vials stored at 4°C and 25°C remained stable for at least 28 d. No physical, chemical or structural instability was found. No aggregation was observed by turbidimetry, SEC and DLS. Hydrodynamic diameters remained unchanged, as chromatographic profiles in CEX and thermal aggregation curves. Functionally, the ability of IPI to antagonise CTLA-4/B7.2 binding remained stable over 1 month at 4°C. Conclusion: These results indicate that unused residues of IPI in their original vials can be safely kept up to 28 d, following good manufacturing procedures, allowing re-use for another patient or in case of cold-chain rupture. Highlights: Ipilimumab in original vial (5 mg/ml) was physico-chemically and functionally stable for 28 d after opening at 4°C and 25°C. Extended stability of ipilimumab could allow physicians to develop new therapeutic applications like intratumoural injection. In hospital pharmacies, unused residues of ipilimumab could be pooled for different patients, permitting an important cost saving. In case of unexpected short-time cold-chain rupture, ipilimumab vials don't have to be discarded.